Political ideology and the discursive construction of the multinational hotel industry. (June 2018) - Maclean, Mairi; Harvey, Charles; Suddaby, Roy; O'Gorman, Kevin
How might political ideology help to shape an organizational field? We explore the discursive construction of the multinational hotel industry through analysis of one of its leading actors, Hilton International (HI), conceived by Conrad Hilton as a means of combatting communism by facilitating world peace through international trade and travel. While the politicized rhetoric employed at hotel openings reflected institutional diversity, it resonated in parallel with a strong anti-communist discourse. We show that through astute political sensemaking and sensegiving, macro-political discourse that is ideological and universalizing may be allied to micro-political practices in strategic action fields. Our study illuminates the processes of early-stage post-war globalization and its accompanying discourses, demonstrating that the foundation of a global industry may be ideologically inspired. Our primary contribution to theory is specific acknowledgement of the importance of political ideology as a particular 'social skill', helping to determine how international business has been 'won'.